Importance of markers of hepatitis B virus in alcoholic liver disease. - Saunders, J B (1983)
To determine the importance of the presence of serological markers of hepatitis B virus infection in patients with alcohol related liver disease we compared cumulative alcohol intake and clinical and histological features in patients with markers of hepatitis B virus infection and in those without. Hepatitis B surface antigen (HBsAg) was detected in five (2%) out of 285 patients studied and antibody to HBsAg (anti-HBs) in 41 (14%); one patient had antibody to hepatitis B core antigen alone. The combined prevalence of markers of hepatitis B virus infection was similar in patients with alcoholic cirrhosis (18%) and precirrhotic liver disease (13%). Two patients positive for HBsAg had histological features of both alcoholic liver disease and chronic active hepatitis, with stainable HBsAg. Patients with anti-HBs were, however, histologically indistinguishable from patients without markers, and the mean cumulative alcohol intake of patients with anti-HBs was similar to or even higher than that of patients with liver disease of comparable severity who had no evidence of previous infection. The presence of markers of hepatitis B virus infection was related to former residence in countries with a high prevalence of the infection and to previous parenteral treatment and blood transfusions. Infection with hepatitis B virus does not enhance the development of chronic liver disease in heavy drinkers, except in the small number who remain positive for HBsAg.